ASI sebagai faktor protektif terhadap autisme - Kornelius Dandung Bawono; Elisabeth Siti Herini; Setya Wandita (Jurnal Gizi Klinik Indonesia, 2012)
Background: The prevalence of autism has risen in the last decades. Risk factors of autism remain controversial and were thought to be multifactorial. One hypothesis stated that it may be caused by leaky gut theory and long chain polyunsaturated fatty acid defi ciency. Optimal duration of breastfeeding has been proven to reduce risk of gastrointestinal infection and improve child’s cognitive ability.Objective: To study the protective effect of optimal duration of breastfeeding to reduce the risk of autism. Method: A matching case-control study was conducted in Yogyakarta and Magelang during 2008. Inclusion criteria of case group were all children with autism (diagnosed based on DSM-IV TR criteria), aged 3-10 years. Autistic children with distinct genetic disorder were excluded. Control group was matched on gender, age, and their residence. Breastfeeding pattern and other related information were obtained by direct interview. McNemar test, conditional multivariate logistic regression, and Maentel-Haenszel test were used to fi nd factors that are signifi cantly associated with autism.Result: There were 52 children with autism and 104 control subjects. The mean age was 5 years old. The analysis revealed that breastfeeding duration for less than 6 months was a signifi cant risk factor for autism (ORMH=2,05; RK 95%:1,03-5,01), as well as history of abnormal birth weight (OR=3,36; RK 95%:1,37-8,44). There was dose-effect gradient as breastfeeding duration affected risk of autism. There was no differences on the duration of exclusive breastfeeding between the two groups. Conclusion: Breastfeeding duration of less than 6 months was a signifi cant risk factor for autism.